Perancangan Komunikasi Visual CD Interaktif “Serial Polisi Cilik” Guna Menanamkan Kesadaran Tertib Lalu Lintas Sejak Dini - Darmawan, Andreas James; Effendy, Willya (Bina Nusantara University, 2011)
Along with the increasing number of accidents in large cities, should the role of visual communication is also increasingly necessary. Its role is as a maker of communications media that attract, encourage, and interactive. So message traffic rules to be conveyed can be conveyed with good and embedded in the consciousness of the receiver behave. For this role of visual communication